2014
DOI: 10.1209/0295-5075/107/57008
|View full text |Cite
|
Sign up to set email alerts
|

Bi 2 Te 3−x Se x series studied by resistivity and thermopower

Abstract: -We study the detailed temperature and composition dependence of the resistivity, ρ(T ), and thermopower, S(T ), for a series of layered bismuth chalcogenides Bi2Te3−xSex, and report the stoichiometry dependence of the optical band gap. In the resistivity of the most compensated member, Bi2Te2.1Se0.9, we find a low-temperature plateau whose onset temperature correlates with the high-temperature activation energy. For the whole series S(T ) can be described by a simple model for an extrinsic semiconductor. By s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The measurement of thermopower on a sample from the same batch showed that the charge carriers in the sample are electrons. 35…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of thermopower on a sample from the same batch showed that the charge carriers in the sample are electrons. 35…”
Section: Resultsmentioning
confidence: 99%
“…compositional gradient [1] or lightly doped Bi 1.9 Tl 0.1 Te 3 samples (28 mΩcm) [17]. However, they are lower than those obtained for heavy chemical doping in the Bi 2 -Te x 3 Se x system (1-20 Ωcm for = x 0.9 1 -) [5,10,12]. It should be noted that although Bi 2 Te 2 Se has the same crystal structure as Bi 2 Te 3 and is commonly referred to as chemically doped Bi 2 Te 3 , the electronic structures of the two compounds are in fact quite different, particularly near the band edges.…”
mentioning
confidence: 76%
“…Since it does not seem realistic that insulating Bi-based bulk TI samples can be achieved by reducing only the defect density [9], it is necessary to compensate the carriers already present to push the Fermi level inside the bandgap. In Bi 2 Te 3 , compensation can be realized either by chemical doping, e.g., Bi 2 -Te x 3 Se x [5][6][7]10], or as recently proposed, by doping using irradiation-induced defects [11]. Irradiations performed on Bi 2 Te 3 at room temperature showed that the created defects act as electron donors and can thus be used to change the conduction from p-to n-type.…”
mentioning
confidence: 99%
“…The aforementioned interaction of the n-type defects with the p-type ones leads to the inaccurate determination of carrier concentration derived from volume-averaged (i.e. integral) techniques such as Seebeck coefficient measurements [15,[29][30][31]. In contrast to electrical transport methods, the NMR lineshape and T 1 measurements allow for a site-specific characterization of the electronic band structure [14] due to their proportionality to the effective mass and the carrier density.…”
Section: Resultsmentioning
confidence: 99%